2005
DOI: 10.1248/cpb.53.1372
|View full text |Cite
|
Sign up to set email alerts
|

Compounds Structurally Related to Tamoxifen as Openers of Large-Conductance Calcium-Activated K+ Channel

Abstract: We found that a variety of compounds containing partial structures of tamoxifen showed activity as chemical modulators of large-conductance calcium-activated K ؉ channels (BK channels).Key words large-conductance calcium-activated K ϩ channel; tamoxifen; channel opener; (xeno)estrogen; electrophysiology Large-conductance calcium-activated K ϩ channels (BK channels) characteristically respond to two distinct physiological stimuli, i.e., changes in membrane voltage and in cytosolic Ca 2ϩ concentration.1) The BK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…We synthesized several Tam-inspired compounds bearing identical substituents on one carbon atom of the olefin, 12 and found that two of them were potent inhibitors of astrocyte L-Glu transporters. The diethyl-substituted derivative 1 inhibited L-Glu transporters in the picomolar range (62.7 ± 7.48% of control at 1 pM; Figure 2A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We synthesized several Tam-inspired compounds bearing identical substituents on one carbon atom of the olefin, 12 and found that two of them were potent inhibitors of astrocyte L-Glu transporters. The diethyl-substituted derivative 1 inhibited L-Glu transporters in the picomolar range (62.7 ± 7.48% of control at 1 pM; Figure 2A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This structural complexity makes the stereospecific synthesis of Tam-related derivatives difficult. We thus focused on Tam-inspired compounds bearing identical substituents on at least one of the olefinic carbon atoms . It is well-known that the N , N -dimethylaminoethyl substituent on the phenolic oxygen atom and the regiochemistry of the tetrasubstituted olefin of Tam are crucial for ER binding activity .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, besides their ample structural and chemical diversity, even exact comparisons between analogues described in different studies cannot be simply made, particularly because of the diversity of indications for which they are claimed as well as the plethora of the techniques and pharmacological models by which they are tested. The wide variety of different natural compounds [98], such as flavonoids and synthetic analogues [99,100], pimarane diterpenes and synthetic analogues [101][102][103], and other synthetic drugs, including tamoxifen and analogues [104] [105], anti-inflammatory fenamates [106] (Fig. (6)), chlorzoxazone [107] (Fig.…”
Section: Structure Activity Relationshipsmentioning
confidence: 99%